Penggunaan Metode QFD Menerjemahkan Suara Konsumen Untuk Pengembangan Lip Product Lavine Beaute - Kurniawan, Shelvy; Nahdi, Nabila Dian (Bina Nusantara University, 2020)
This study aims to bridge the literature gap to examine factors that influence customers in buying a beauty product especially product quality.Â The type of research used is descriptive. The use of the method in this study is the quality function deployment (QFD) method which has 6 parts namely; customer needs, technical attributes, relationship matrix, technical assessment, correlation matrix, and competitive assessment. The findings of this study are the attributes that meet BPOM standards, ingredients performance, and the probability of failure become one of the attributes that have the highest value on the part of customer needs that can meet customer satisfaction in product development.